Estudo de caso sobre as emissões de gases do efeito estufa em uma termoelétrica do RS - (:unkn) unknown (Universidade Federal do Pampa, 2022)
The water crisis not only affects water supply but also has an impact on energy production, as hydroelectric generation predominates in Brazil. During periods of drought, such as in 2021, energy production relies on thermal power plants. Fossil fuel power plants are the main source of greenhouse gas (GHG) emissions in the Brazilian electricity sector. Therefore, evaluating the implications of thermal power generation on atmospheric pollutant and GHG emissions is an important step towards a discussion on electricity generation and the necessary integration between energy and environmental policies. Thus, this study presents an analysis of GHG emissions related to thermal energy production. The Greenhouse Gas Emissions Inventories of the Eletrobras group companies from 2016 to 2021 were consulted. The case study presented the data from the Southern Brazil Power Generation and Transmission Company (CGT Eletrosul), located in the city of Candiota, RS. It was demonstrated that there was a reduction of approximately 48% in CO2e emissions between 2019 and 2020, despite a 35% increase in energy generation. However, the emissions reduction target is not being achieved. Based on these aspects, the importance of diversifying the national electricity matrix was emphasized, including alternative fuel sources and renewable energy, to contribute to the fulfillment of GHG emissions reduction targets and the achievement of the Sustainable Development Goals (SDGs) of the 2030 Agenda.
Keywords: Termoelétrica; Energia; Gases de Efeito Estufa; Emissões; Thermoelectric; Energy; Greenhouse Gases; Emissions; CNPQ::ENGENHARIAS